1965
DOI: 10.1210/endo-77-4-609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyrotropin Releasing Factor (TRF) of Ovine, Bovine, Porcine and Human Origin on Thyrotropin Releasein Vitroandin Vivo

Abstract: Peptide-like materials which release thyrotropin (TSH) from the pituitary in vivo and in vitro were obtained from the hypothalamus of the ox, sheep and pig and from human neurohypophysial tissue. Thyrotropic hormone releasing factor (TRF) activity was measured in vitro by the isolated rat pituitary incubation method of Saffran and Schally. TSH secreted into the medium was assayed by the release of 13I I from the thyroid gland of the mouse as described by McKenzie and by the uptake of 131 I by the tadpole's thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…TRH (also known as thyrotropin-releasing factor or thyroliberin) was first isolated and sequenced in the 1960s [ 68 – 70 ]. In mammals, TRH is produced in the hypothalamus, and stimulates the release of thyroid-stimulating hormone (TSH) and prolactin from the anterior pituitary [ 71 , 72 ]. The recent discovery of a TRH receptor in the annelid Platynereis dumerilii indicates that the evolutionary origin of this neuropeptide signalling system predates the divergence of protostomes and deuterostomes [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…TRH (also known as thyrotropin-releasing factor or thyroliberin) was first isolated and sequenced in the 1960s [ 68 – 70 ]. In mammals, TRH is produced in the hypothalamus, and stimulates the release of thyroid-stimulating hormone (TSH) and prolactin from the anterior pituitary [ 71 , 72 ]. The recent discovery of a TRH receptor in the annelid Platynereis dumerilii indicates that the evolutionary origin of this neuropeptide signalling system predates the divergence of protostomes and deuterostomes [ 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…TRH (also known as thyrotropin-releasing factor or thyroliberin) was first isolated and sequenced in the 1960s [68–70]. In mammals, TRH is produced in the hypothalamus and stimulates the release of thyroid-stimulating hormone (TSH) and prolactin from the anterior pituitary [71, 72]. The recent discovery of a TRH receptor in the annelid Platynereis dumerilii indicates that the evolutionary origin of this neuropeptide signaling system predates the divergence of protostomes and deuterostomes [73].…”
Section: Resultsmentioning
confidence: 99%
“…Schreilber was the first to use the in vitro system of Saffran and Schally( 15) for detection af stimlaition of TSH release in vitro(24). However, the T R F preparations used in studies reported here are 1O, OOO-1OO, OOO times more aotive than thorie reported previously (26,27). Solomon (27) utilized it for partially purified T R F prepallations fm various s p i e s .…”
Section: Adidition Of T4 As In Experiments Shown Inmentioning
confidence: 83%
“…However, his criteria for TSH release were very indirect and based on activation of hyplophysial phosiphstarses. The effect Olf T R F on pituitary TSH release can be contrasted with the action of U-and P-MSH, which stimulate the thyroid (20)(21)(22), presumably by a direat action, since they are active in hypophysectomized animals (20) and have no effect on release of TSH from rat pituitaries in vitro ( 26,27). However, the T R F preparations used in studies reported here are 1O, OOO-1OO, OOO times more aotive than thorie reported previously (26,27).…”
Section: Adidition Of T4 As In Experiments Shown Inmentioning
confidence: 99%